Biological activity of some plant extracts in Diyala Governorate (Eurasian Research Bulletin, 2022)
The goal of this work was to determine the antimicrobial activity of wild plants found in Diyala (Nerium oleander, Peganum harmala, and Alhagi mauroram), whose active components (alkaloids and glycosides) were extracted using a hot alcoholic extract. In this work, several solutions were made and the antibacterial activity of Escherichia coli was tested using the Minimum Inhibitor Concentration (MIC) technique at various concentrations. PCR was used to test the extracts' activity against the ddpC gene. The study samples revealed five mutations: three substitution mutations and two silent mutations, indicating that plant extracts have good efficacy due to the presence of effective compounds capable of inhibiting microbial growth as well as a clear effect on DNA by controlling enzymes, transcription, and translation processes in DNA bacteria. Due to the urgent and ongoing need to detect new antimicrobials with diverse chemical structures and valuable mechanisms of action, it is possible to make good use of the species of wild plants found throughout Diyala city. This is because there is an increase in the incidence of new and frequent infectious diseases as a result of antibiotic resistance.